2012
DOI: 10.1364/ol.37.003030
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional photonic component for multichannel coherence measurements

Abstract: We present the experimental results of a three-dimensional integrated photonic component designed for the simultaneous determination of mutual coherence properties of three light channels. Potential applications to astronomical optical interferometry are proposed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
(27 reference statements)
0
19
1
Order By: Relevance
“…We have a stability better than λ∕36 over the whole bandwidth of 50 nm with a minimum value of λ∕58 at a wavelength of 650 nm. These values are higher than what reported previously with a DBC component [20], but we point out that the condition number of the α-matrix in previous measurements was lower than in the present case (4.5 instead of 10). Notice that planar beam combiners for astronomical interferometry were reported to have a closure phase stability of λ∕144 at a wavelength of 1550 nm [13].…”
Section: B Uniformity Of Dbc Performance As a Function Of Wavelengthcontrasting
confidence: 91%
See 2 more Smart Citations
“…We have a stability better than λ∕36 over the whole bandwidth of 50 nm with a minimum value of λ∕58 at a wavelength of 650 nm. These values are higher than what reported previously with a DBC component [20], but we point out that the condition number of the α-matrix in previous measurements was lower than in the present case (4.5 instead of 10). Notice that planar beam combiners for astronomical interferometry were reported to have a closure phase stability of λ∕144 at a wavelength of 1550 nm [13].…”
Section: B Uniformity Of Dbc Performance As a Function Of Wavelengthcontrasting
confidence: 91%
“…It consists of a square 4 × 4 array of single-mode waveguides (cutoff wavelength much shorter than 640 nm), which is suitable for the combination of three different beams. This sample differs from previous ones [20] by the fact that the waveguides are not running parallel through the sample but have a diverging pitch. The lattice period of the array ranges from 13 μm at the input to 80 μm at the output.…”
Section: A General Layoutmentioning
confidence: 89%
See 1 more Smart Citation
“…Characterised in an interferometric test bed, the beam combiner achieved > 99% monochromatic fringe visibility and 21% fringe visibility with broadband light ranging from 3 to 11 µm. Whilst this beam combiner was based on a linear network of Y-junctions derived from planar beam combiners, it has been shown that fringe visibility and closure phase can also be retrieved by injecting light into a 2D array of evanescently coupled waveguides [133]. This approach potentially offers scalability to a large number of inputs in a compact chip [134].…”
Section: Beam Combiningmentioning
confidence: 99%
“…A novel approach is for instance the discrete beam combiners (DBC 43 ), a combination concept based on the properties of light propagation in 2D periodic arrays of straight, evanescently coupled waveguides. DBC require an array of at least M = N tested in the laboratory with monochromatic 46 and polychromatic 47 light in the R-band. DBC show no waveguide crossovers or bending and make them potential candidates for high-throughput IO devices.…”
Section: Long-baseline Interferometrymentioning
confidence: 99%